АНАЛІЗ ЕЛЕКТРОМАГНІТНИХ ПРОЦЕСІВ У КОЛАХ З НАПІВПРОВІДНИКОВИМИ ПЕРЕТВОРЮВАЧАМИ З СІМНАДЦЯТИЗОННИМ РЕГУЛЮВАННЯМ ВИХІДНОЇ НАПРУГИ - Сенько, В.І.; Михайленко, В.В.; Юрченко, М.М.; Юрченко, О.М.; Чуняк, Ю.М. (Інститут електродинаміки НАН України, Київ, 2016)
Study of the electromagnetic processes was organized beside robot in electric circuit with semiconductor commutator. It created a mathematical model of the semiconductor converter with an active–inductive load and with multi-channel zone regulation phase voltages disregarding losses in the semiconductor commutator. It is developed a method of multivariable function, which is a part of algorithmic equations for steady-state and transient processes analysis in networks with semiconductor commutators and reactive elements for using of phase voltage. The broughted graphs that display the electromagnetic processes in electric circuit. References 3, figures 2.